Fundamental solutions of anomalous diffusion equations with the decay exponential kernel - Yang, Xiao-Jun; Feng, Yi-Ying; Cattani, Carlo; İnç, Mustafa (Wiley, 2019)
In the letter, we consider the anomalous diffusion equations involving the general derivatives with the decay exponential kernel for the first time. With the use of the Laplace transform, the analytical solutions with graphs are discussed in detail. The results are accurate and efficient in the description of the behaviors of the anomalous diffusion problems.
Keywords: analytical solution; anomalous diffusion equations; decay exponential kernel; general derivatives; Laplace transform